Impact of p38 mitogen-activated protein kinase inhibition on immunostimulatory properties of human 6-sulfo LacNAc dendritic cells - Langosch, Saskia; Wehner, Rebekka; Malecka, Ania; Franks, Hester A.; Schäkel, Knut; Bachmann, Michael; Jackson, Andrew M.; Schmitz, Marc (Elsevier, 2016)
p38 Mitogen-activated protein kinase (MAPK) plays a crucial role in the induction and regulation of innate and adaptive immunity. Furthermore, p38 MAPK can promote tumor invasion, metastasis, and angiogenesis. Based on these properties, p38 MAPK inhibitors emerged as interesting candidates for the treatment of immune-mediated disorders and cancer. However, the majority of p38 MAPK inhibitor-based clinical trials failed due to poor efficacy or toxicity. Further studies investigating the influence of p38 MAPK inhibitors on immunomodulatory capabilities of human immune cells may improve their therapeutic potential. Here, we explored the impact of the p38 MAPK inhibitor SB203580 on the pro-inflammatory properties of native human 6-sulfo LacNAc dendritic cells (slanDCs). SB203580 did not modulate maturation of slanDCs and their capacity to promote T-cell proliferation. However, SB203580 significantly reduced the production of pro-inflammatory cytokines by activated slanDCs. Moreover, inhibition of p38 MAPK impaired the ability of slanDCs to differentiate naïve CD4(+) T cells into T helper 1 cells and to stimulate interferon-γ secretion by natural killer cells. These results provide evidence that SB203580 significantly inhibits various important immunostimulatory properties of slanDCs. This may have implications for the design of p38 MAPK inhibitor-based treatment strategies for immune-mediated disorders and cancer.